Malignant insulinoma: spectrum of unusual clinical features - Hirshberg, Boaz (2005)
BACKGROUND: Malignant insulinoma occurs in a few patients with insulinoma. Due to the small sample of patients, there are little data regarding their clinical manifestation as well as the preferred treatment modalities. The aims of the current study were to summarize the National Institutes of Health experience during the last two decades and to conduct a critical review of the current literature. METHODS: The authors identified 10 patients with metastatic insulinoma. RESULTS: The patients presented with four patterns of clinical behavior. First, four patients presented with lymph node metastasis and, after surgical excision, maintained a prolonged tumor-free survival. Second, four patients presented with metastatic disease to the liver, which appeared years after the initial diagnosis and presumed curative surgery. Third, one patient presented with a large α-fetoprotein-secreting liver mass. Finally, 9 of the 10 patients had a prolonged survival. Various treatment modalities were used to control hypoglycemia. Short-term benefits were most often achieved with embolization and diazoxide. Less successful modalities included radiofrequency ablation, radical debulking surgery, verapamil therapy, octreotide therapy, and chemotherapy. CONCLUSIONS: The current study, as well as others, suggested that metastatic insulinoma may have a variable natural history. After the initial surgical resection, the biology of the tumor, rather than any treatment modality, was most likely the major determinant of long-term survival. Published 2005 by the American Cancer Society.